ENDOVASCULAR METHODS OF DIAGNOSTICS AND TREATMENT OF CARDIOVASCULAR DISEASES - L. S. Kokov (Неотложная медицинская помощь)
Endovascular methods of diagnostics and treatment of cardiovascular diseases.